ʼJaʼ tshon pod drug gi dbaṅ dpe : initiation texts for the rediscovered cycles revealed by ʼJaʼ-tshon-sñiṅ-po - Sna-tshogs-raṅ-grol, Rtse-le Rgod-tshaṅ-pa, b. 1608; Ṅag-dbaṅ-mthar-phyin (Tobdan Tsering, 1978)
Vajrayana Buddhist initiation texts of the Nyingmapa tradition.